Purchase intention to virtual influencer marketing: Social presence theory highlights authenticity over influencer type - Erika Putri Wulandari; Steffen Hasta; Yolanda Masnita; Husna Leila Yusran (Nur Science Institute, 2026)
Purchase intention endorsed by virtual influencers remains inconsistent across studies, leaving a practical gap in how exposure translates into buying. This study examines whether anthropomorphic appearance and behavior increase purchase intention via social presence and perceived authenticity, and whether influencer type matters. Guided by Social Presence Theory, we conducted a cross-sectional online survey; the hypothesized relationships were evaluated using SEM. Results show that anthropomorphic appearance and behavior significantly heighten social presence, social presence increases perceived authenticity, and perceived authenticity strongly predicts purchase intention. Conversely, influencer type shows no meaningful effect on authenticity and does not improve the indirect pathway from anthropomorphism to purchase intention. The findings recommend that practitioners prioritize human-like visual and behavioral cues and design interactions that cultivate social presence and authenticity rather than relying on celebrity status. Limitations include the cross-sectional design, use of a single virtual influencer stimulus, and a relatively homogeneous sample; future work should test multiple stimuli using longitudinal designs.